The Mass Spectrum Analyzer (MSA) on board the BepiColombo MMO. Issue 7 (4th July 2016) - Delcourt, D.; Saito, Y.; Leblanc, F.; Verdeil, C.; Yokota, S.; Fraenz, M.; Fischer, H.; Fiethe, B.; Katra, B.; Fontaine, D.; Illiano, J.‐M.; Berthelier, J.‐J.; et al.
Abstract: Observations from the MESSENGER spacecraft have considerably enhanced our understanding of the plasma environment at Mercury. In particular, measurements from the Fast Imaging Plasma Spectrometer provide evidences of a variety of ion species of planetary origin (He +, O +, and Na + ) in the northern dayside cusp and in the nightside plasma sheet. A more comprehensive view of Mercury's plasma environment will be provided by the BepiColombo mission that will be launched in 2018. On board the BepiColombo MMO spacecraft, the Mercury Plasma/Particle Experiment consortium gathers different sensors dedicated to particle measurements. Among these sensors, the Mass Spectrum Analyzer (MSA) is the instrument dedicated to plasma composition analysis. It consists of a top hat for energy analysis followed by a time‐of‐flight (TOF) chamber to derive the ion mass. Taking advantage of the spacecraft rotation, MSA will measure three‐dimensional distribution functions in one spin (4 s), from energies characteristic of exospheric populations (in the eV range) up to plasma sheet energies (up to ~38 keV/q). A notable feature of the MSA instrument is that the TOF chamber is polarized with a linear electric field that leads to isochronous TOFs and enhanced mass resolution (typically, m /∆ m  ≈ 40 for ions with energies up to 13 keV/q). At Mercury, this capability is of paramount importance to thoroughly characterize the wide variety of ion species originating from the planet surface. It is thus anticipated that MSA will provide unprecedented information on ion populations in the Hermean environment and hence improve our understanding of the coupling processes at work. Key Points: The MSA instrument of BepiColombo MMO will measure three‐dimensional mass‐resolved ion distribution functions in Hermean magnetosphere Thanks to seldom flown reflectron technique that is used for measuring time of flights, mass resolution is greatly enhanced (m/Dm > 40) Measurements with high time resolution (about MMO spin period) will allow detailed analysis of the dynamics of ions of planetary origin